UPAYA MELESTARIKAN KEARIFAN LOKAL BATIK KONTEMPORER DI DESA SENDANG LAMONGAN - Cahya utami, Okky Ambarita; Utami Agustin, Indri Ati; Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Contemporary batik is a form of local wisdom that still exists in the current era. Therefore, local wisdom must always be protected and cared for by the next generation. The aim of this research is to describe efforts to preserve the local wisdom of contemporary batik in Sendang village. This is considered important because with the dynamic conditions of the times, it is feared that local culture will be eroded and cause culture to disappear. This research approach is qualitative, using library methods and interviews with each owner. The object of this research is Sendang contemporary batik, while the author digs up data from contemporary batik entrepreneurs in Sendang village, namely Mas Yurik Sya'bana, owner of UD Bahana, Mrs. Sukaryawati, owner of AFIQ JAYA batik business, and Mrs. Lathifah Luthfiana, owner of Galeri Batik Nusantara batik business. The results can be seen that to maintain and preserve the local wisdom of contemporary batik in Sendang village is through training efforts, holding batik exhibition events, maintaining quality, and much more.